Effect of Employee Performance Factors on Corporate Performance: Evidance in Information Technology Firm - Lina Suciati (EkBis: Jurnal Ekonomi dan Bisnis, 2019)
The MNC (Multinational) company based in California is a computer storage and data management (storage) company. PT. NetApp is very concerned about the welfare of its employees. All NetApp achievements are inseparable from good management of its human resources, in this context the performance of its employees. Although NetApp is one of the best companies at work, the percentage of employee turnover has increased from year to year. This type of research is quantitative research. Sugiyono (2007) Quantitative data is data in the form of numbers, or qualitative data that is called up (scoring). This study is intended to determine the relationship between the seven variables, namely Recruitment of Independent Variables (X1) and Career Path (X2), namely Corporate Performance Dependent variable (Y) and Employee Performance (Z) as a variable intervening. After a statistical test, the results are obtained: first the recruitment variable has a significant effect on corporate performance variables. This means that recruitment is the initial stage of the employee to enter into a company. not significant to corporate performance variables